Sex and ABO Blood Differences in SARS-CoV-2 Infection Susceptibility - Mahmut Cerkez Ergoren; Gokce Akan; Emrah Guler; Gulten Tuncel; Damla Akovalı; Emine Unal Evren; Hakan Evren; Huseyin Kaya Suer; Tamer Sanlidag (Global Medical Genetics)
Data consisting of millions of cases cannot still explain the immunopathogenesis mechanism between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and host cell for ongoing coronavirus disease 2019 (COVID-19) pandemics. Epidemiological studies among different populations suggested different impacts of ABO and Rh antibodies on the COVID-19 susceptibility. Thus, the ABO blood group and the SARS-CoV-2 infection paradox remain unclear. Therefore, the present retrospective case–control study aimed to investigate the possible association between ABO blood groups and Rh blood types on SARS-CoV-2 infection in the Turkish Cypriot population. A total of 18,639 Turkish Cypriot subjects (297 SARS-CoV-2 COVID-19 patients and 18,342 healthy) were included in this study. Personal and clinical characteristics including age, gender, SARS-CoV-2 infection status, the ABO blood group and Rh blood types were evaluated and compared between two groups. As a result, ABO blood group was shown to be associated with a higher risk of SARS-CoV-2 infection as well as with male sex (p = 0.018). There was no association between Rh blood type and COVID-19. Overall, this study is the first largest sample group study to show the distribution of ABO blood group and Rh blood types in the healthy Turkish Cypriot population. Based on the current evidence, there are insufficient data to guide public health policies regarding COVID-19 pathogenesis.